Study of prescription pattern of drugs used in the treatment of osteoarthritis in a tertiary care teaching hospital: an observational study - Gupta, Rohini; Malhotra, Apoorva; Malhotra, Pavan (International Journal of Research in Medical Sciences, 2018)
Background: Osteoarthritis(OA) is a major cause of chronic pain and lower extremity disability among the elderly due to its predilection for lower extremity joints such as the knee and hip. Although Paracetomol is the initial drug of choice, NSAIDS are also frequently used in the symptomatic relief of osteoarthritis. But still, there is a need for safe and effective alternative treatments which would provide both symptomatic improvement and disease modifying effects in OA. The primary objective was to study the prescribing pattern of drugs used in the treatment of osteoarthritis. Methods: A cross-sectional, prospective, observational study was conducted on newly diagnosed as well as old treated patients with osteoarthritis from orthopaedic outpatient department in a tertiary care teaching hospital. A total of one hundred and eighty-eight patients were enrolled after screened for the inclusion and exclusion criteria. Data was recorded in a specially designed proforma which include information regarding the demographic profile of the patients and about the pattern of drugs prescribed. Results: Out of one hundred eighty-eight patients who were affected with Osteoarthritis, females (57.9%) were more commonly affected than males (42%). OA knee (77%) either unilateral or bilateral was most commonly affected, followed by hip joint, spine and other joints. NSAIDS were more frequently prescribed in 76.6% patients than paracetamol which was prescribed in only 34 % of patients and that only in combination with NSAIDS and opioids. Various other drugs were also used as adjunct therapies that included gastroprotective agents in 49% of patients, Calcium in 54% of patients, Vitamin D3 supplements in 51% of patients and symptomatic slow acting drugs for OA (SYSADOA) which included diacerin and glucosamine sulfate as combination in 11% of patients. Conclusions: Our study showed Osteoarthritis knee being most common among female patients. Paracetamol and SYSADOA being under prescribed and NSAIDS are the most frequently used drugs in OA. National drug policy is needed to rationalize the drug use and bring awareness among the prescribing doctors.